Extrapolation of Efficacy from Adults to Pediatric Patients of Drugs for Treatment of Partial Onset Seizures: A Regulatory Perspective. Issue 4 (3rd July 2022) - Mehrotra, Shailly; Bhattaram, Atul; Krudys, Kevin; Bewernitz, Michael; Uppoor, Ramana; Mehta, Mehul; Liu, Tao; Sheridan, Philip; Hershkowitz, Norman; Kozauer, Nicholas; Bastings, Eric; Dunn, Billy; et al.
Abstract : The US Food and Drug Administration (FDA) has concluded that the efficacy of drugs approved for the treatment of partial onset seizures (POS) in adults can be extrapolated to pediatric patients 1 month of age and above and that independent efficacy trials in this pediatric population are no longer needed. This paper focuses on the dosing, pharmacokinetic (PK), exposure‐response, and clinical information that were leveraged from the approved drugs for the treatment of POS to conduct analyses that supported extrapolation of efficacy in pediatric patients. Clinical data from trials for eight drugs (levetiracetam, oxcarbazepine, topiramate, lamotrigine, gabapentin, perampanel, tiagabine, and vigabatrin) approved in both adults and pediatric patients for the treatment of POS were analyzed. Comparisons of exposures at approved doses, placebo response, and model‐based exposure‐response relationships were performed. Based on disease similarity, similar response to intervention, and similar exposure‐response relationships in adults and pediatric patients, it was concluded that extrapolation of efficacy in pediatric patients aged 1 month and above is acceptable. PK analysis to determine pediatric dose and regimens that provide drug exposure similar to that known to be effective in adult patients with POS will be required, along with long‐term open‐label safety data in pediatric patients.